A History of Anti-VEGF Inhibitors in the Ophthalmic Literature: A Bibliographic Review. (July 2021) - Whitescarver, Todd D.; Hobbs, Samuel D.; Wade, Christian I.; Winegar, Jordan W.; Colyer, Marcus H.; Reddy, Ashvini K.; Drayna, Paul M.; Justin, Grant A.
Purpose: This work aimed to analyze the 100 most-cited articles on antivascular endothelial growth factor (anti-VEGF) inhibitors. Methods: A literature search for anti-VEGF inhibitors using the Web of Science was completed using the bibliographic databases for peer-reviewed literature published in Ophthalmology, the New England Journal of Medicine, Journal of the American Medical Association, and Lancet . Primary outcomes were the most frequently cited articles and journals with the most citations as well as the specific drug and disease process studied. Results: There were 42 696 cumulative citations among the top 100 articles. The articles were published between 2004 to 2016, with most articles published in 2006. Ophthalmology published the greatest number of articles among the top 100 at 48, whereas the New England Journal of Medicine has the most citations per publication at 1714. Ranibizumab was the medication researched in most articles at 56, followed by bevacizumab at 48, aflibercept at 10, and pegaptanib at 9. Forty-two articles investigated treatment of age-related macular degeneration, followed by 24 investigating diabetic macular edema, 10 for retinal vein occlusion, 8 for proliferative diabetic retinopathy, 2 for retinopathy of prematurity and polypoidal choroidal vasculopathy, and 1 for corneal neovascularization. Conclusions: As evidenced by the considerable number of citations accumulated over the past 20 years, anti-VEGF inhibitors have led to significant research in ophthalmology.